Shaping of CD56bri Natural Killer Cells in Patients With Steroid-Refractory/Resistant Acute Graft-vs.-Host Disease via Extracorporeal Photopheresis - Ni, Ming; Wang, Lei; Yang, Mingya; Neuber, Brigitte; Sellner, Leopold; Hückelhoven-Krauss, Angela; Schubert, Maria-Luisa; Luft, Thomas; Hegenbart, Ute; Schönland, Stefan; Wuchter, Patrick; Chen, Bao-an; et al. (Frontiers in Immunology, 2019)
CD56bri natural killer (NK) cells play an important role in the pathogenesis of graft-versus-host disease (GVHD) and immune defense in the early period after allogeneic hematopoietic stem cell transplantation. Extracorporeal photopheresis (ECP) as an immunomodulating therapy has been widely used for GVHD treatment. However, the mechanism of action of ECP still remains to be elucidated, particularly the influence of ECP on NK cells. Thirty-four patients with steroid-refractory/resistant acute GVHD (aGVHD) ≥ °II and moderate to severe chronic GVHD (cGVHD) received ECP therapy at the University Hospitals Heidelberg, Greifswald and Tel Hashomer. Patient samples obtained during intensive and long-term treatment were analyzed. Immunomonitoring with respect to cell phenotype and function was performed on rested peripheral blood mononuclear cells (PBMCs) using multiparametric flow cytometry. NK activity in terms of cytokine release was analyzed by intracellular cytokine staining after co-culture with K562 cells. Moreover, the proliferative capacity of NK cells, CD4+ and CD8+ T cells was determined by carboxyfluorescein succinimidyl ester (CFSE) staining. Clinically, 75% of aGVHD and 78% of cGVHD patients responded to ECP therapy. Moreover, our data show that aGVHD, cGVHD patients and healthy donors (HDs) present distinct NK patterns: aGVHD patients have a higher frequency of CD56bri NK subsets with stronger NKG2D and CD62L expression, while CD56-CD16+ NK cells with higher expression of CD57 and CD11b stand out as a signature population for cGVHD. ECP therapy could dramatically decrease CD56briCD16- NK cells with shifting the quality from a cytotoxic to a regulatory pattern and additionally mature CD56dim NK cells via upregulation of CD57 in complete responding aGVHD patients. Moreover, ECP could keep the anti-virus and anti-leukemia effects intact via maintaining specialized anti-virus/leukemia CD57+NKG2C+CD56dim NK cells as well as remaining the quality and quantity of cytokine release by NK cells. The proliferative capacity of effector cells remained constant over ECP therapy. In conclusion, ECP represents an attractive option to treat GVHD without compromising anti-virus/leukemia effects. Shaping of CD56bri NK cell compartment by downregulating the cytotoxic subset while upregulating the regulatory subset contributes to the mechanisms of ECP therapy in aGVHD.